الإطار المفاهيمي لظاهرة الفساد - فريد تومي; إيمان بوقصة (جامعة البليدة 02 لونيسي علي, 2018)
الملخص: يعتبر النمو السريع والعولمة والتقدم التكنولوجي والعلمي، من بين أهم الدوافع التي أدت إلى نمو الفساد وتطور أشكاله، وبالتالي أصبحت النصوص الجزائية التقليدية عاجزة وقاصرة تقريبا عن مواجهة هذه الظاهرة، حيث يعتبر الفساد المالي من أهم وأعقد المواضيع الاقتصادية كونه يؤدي إلى عرقلة النمو الاقتصادي ويعيق التنمية. فعلى الرغم من الكم الهائل للنصوص التشريعية المجرمة لمختلف صور وأشكال الفساد سواء منها الدولية أو الوطنية، إلا أن هناك العديد من الصور تشكل جانبا من المعضلة تفلت من العقاب أو لا تحظى بالتجريم بنص خاص، طالما أن الأساس في القانون الجنائي هو حضر القياس كأهم نتيجة عن مبدأ الشرعية، وهنا نجد أن الفساد المالي كنوع من أنواع الفساد بل ومن أخطر أنواعه على الاقتصاد الوطني والعالمي على السواء. الكلمات المفتاحية: الفساد، الفساد المالي، التهرب الضريبي، الاقتصاد الموازي، الغش الوظيفي. Title of the intervention: The concept of financial corruption and its effects: Summary: Rapid growth, globalization, technological and scientific progress are among the most important factors that led to the growth of corruption and the development of its forms. Consequently, traditional penal texts have become almost incapable of dealing with this phenomenon. Financial corruption is one of the most important and complex economic issues. In spite of the huge number of criminal acts of various forms and forms of corruption, both international and national, many images are part of the dilemma that is not penalized or penalized by a special provision, as long as the basis of criminal law is the most important The principle of legality, and here we find that financial corruption as a kind of corruption and even the most dangerous types of the national economy and the world alike. Keywords: corruption, financial corruption, tax evasion, parallel economy, job fraud.